Economic growth in the age of ubiquitous threats: How global risks are reshaping growth theory - Orlando Gomes (Economics: The Open-Access, Open-Assessment Journal, 2024)
One of the most outstanding accomplishments of the economic science over the last decades is the development of a sound and coherent theory of economic growth. Research in growth theory has demonstrated that significant and systematic increases in well-being are attainable whenever the right formula is implemented. When combined with efficiency, the ingredients of this formula - innovation, the diffusion of ideas, and human capital accumulation - can drive the economy toward a virtuous path of sustained growth. Notwithstanding, this is an overly optimistic view of growth that does not account for the many obstacles that the creation of wealth may encounter. The current essay surveys cutting-edge research on growth theory to conclude in favor of a paradigm shift: the main concern is no longer just with how to correctly combine production inputs, but with how their efficient use is eventually hampered by a large collection of worldwide risks and threats. Global risks come in many shapes (they can be classified as economic, environmental, geopolitical, societal, and technological) but, in any case, they call for a reexamination of growth theory.
Keywords: O41; O33; O43; O44; 330; growth theory; growth models; global risks; economic disasters; rare events